(untitled) (Biological Sciences - PJSIR, 2006)
Some physicochemical and rheological properties of five commercial wheat varieties cultivated in Sindh, Pakistan, namely, Mehran-89, Kiran-95, TJ-83, Anmol-91 and Sarsabz were analyzed. These wheat varieties were obtained from Wheat Research Institute, Sakrand, Sindh, Pakistan in August 2004. The results revealed that the shriveled and broken grains ranged between 0.5 to 9.0%, test weight 75 to 79kg/hectoliter, thousand grain mass 31.8 to 42.2 g, moisture content 10.3 to 10.8%, protein content 11.9 to 15.5%, wet gluten 23 to 39.7%, dry gluten 7 to 12%, gluten index 36.6 to 85.8%, near-infrared (NIR) hardness score 53 to 61, farinograph water absorption 69.1 to 73.3%, dough development time 2 to 4.5 min, dough stability 2 to 11 min, and degree of softening 30 to 100 Brabender unit. The coefficients of correlation (r) between various quality parameters were also calculated. A significantly positive correlation existed between the hardness score and test weight (r = 0.886). The degree of softening was found to be significantly correlated with moisture content (r = 0.943) and gluten index (r = _ 0.886). It was also observed that the capacity of gluten to bind water was positively correlated with farinograph water absorption (r = 0.891).